The risen : a novel - Rash, Ron, 1953- (New York : Ecco, 2016)
Estranged for decades after a turbulent 1969 summer spent with a free-spirited redhead, two brothers are forced by a shocking reminder to confront the past events that divided them.
Keywords: Brothers -- Fiction; Brothers -- Fiction; Family life -- Fiction; Domestic fiction